2023
DOI: 10.1111/epi.17825
|View full text |Cite
|
Sign up to set email alerts
|

Valproate use associated with frontal and cerebellar gray matter volume reductions: A voxel‐based morphometry study

Ji Hye Shin,
Min Ji Song,
Ji Hyun Kim

Abstract: Recent morphometric magnetic resonance imaging (MRI) studies suggested the possibility that valproate (VPA) use is associated with parieto‐occipital cortical thinning in patients with heterogeneous epilepsy syndromes. In this study, we examined the effect of VPA on the brain volume using a large number of homogenous patients with idiopathic generalized epilepsy. Voxel‐based morphometry was used to compare regional gray matter (GM) volume between 112 patients currently taking VPA (VPA+ group), 81 patients not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Part of the difficulty in the mechanistic understanding of VPA-associated autism arises from the population-based nature of the association studies, thus capturing a cohort of patients with autism arising from in utero exposure to VPA has been difficult. Towards an understanding of the network effects of VPA exposure, the impact of VPA use on brain volume was evaluated based on exposure to the drug ( 136 ). In this study, VPA was found to be associated with diminished gray matter in the cerebellum, frontal cortex, and hippocampus, which correlates to the cerebro-cerebellar network connectivity that has previously been discussed and with areas of increased AMPA receptor expression ( Figure 1 ).…”
Section: Autism Associated With Prenatal Anti-seizure Medication Expo...mentioning
confidence: 99%
“…Part of the difficulty in the mechanistic understanding of VPA-associated autism arises from the population-based nature of the association studies, thus capturing a cohort of patients with autism arising from in utero exposure to VPA has been difficult. Towards an understanding of the network effects of VPA exposure, the impact of VPA use on brain volume was evaluated based on exposure to the drug ( 136 ). In this study, VPA was found to be associated with diminished gray matter in the cerebellum, frontal cortex, and hippocampus, which correlates to the cerebro-cerebellar network connectivity that has previously been discussed and with areas of increased AMPA receptor expression ( Figure 1 ).…”
Section: Autism Associated With Prenatal Anti-seizure Medication Expo...mentioning
confidence: 99%